KARAKTERISTIK FISIK, KIMIA DAN SIFAT ORGANOLEPTIK TEPUNG BERAS MERAH BERDASARKAN VARIASI LAMA PENGERINGAN - Fajar Indriyani; Nurhidajah -; Agus Suyanto (Universitas Muhammadiyah Semarang, 2013)
Brown rice has advantages for health but underused, most choose to consume white rice. Brown rice flour already exist in the market but has not been widely used, so it is necessary to study on the analysis of physical, chemical and organoleptic properties of brown rice flour. based on the variation of drying time 0, 2, 4, 6 hours. Types of brown rice varieties used are Mandel Handayani and Segreng. Physical measurements include yield, color, density Kamba, and water absorption index. Furthermore, chemical analysis include moisture content, ash, protein, fat, fiber and antioxidant activity. Organoleptic test using hedonic test. The results of the study, the best brown rice flour from physical characteristics, and chemical properties are varieties of Mandel Handayani (drying time 2 hours) except Kamba density, water absorption index and fat. Drying time did not significantly affect the organoleptic value.